Penghayatan akidah transgender mak nyah muslim melalui amalan taubat Imam Al-Ghazali - Norhidayah, Haji Mohamad Nawawy (2021)
This study aims to explore the experience of transgender mak nyah muslim and the issue of faith that they face when becoming transgender mak nyah. At the end, the study will be able to produce a concept of repentance that can be applied to the transgender mak nyah based on the thoughts of al-Imam al-Ghazali. This study on transgender belief of mak nyah muslim employs a qualitative research methodology framework using case study design. According to the researcher, this is the most suitable method to be used especially in exploring experiences, identifying issues of faith and finally producing the concept of repentance that can be applied to transgender people through the al-Ghazali’s concept of faith namely al-Ilahiyyah, al-Nabawiyyah and al-Sam’iyyah. In addition to this case study, the researcher has chosen a total of five authoritative respondents who have identified themselves as former transgender mak nyah who have repented and to be the main sample in this study. For that purpose, the researcher has used triangulation techniques by using three methods of data collection through the method of 5 sets of in-depth interviews, 5 sets of observation checklists and 46 analysis documents while 5 study participants are as source data. These three techniques have been compiled and incorporated into NVivo-12 software to create construct validity and reliability. The reliability of the data is obtained through expert validation based on the consensus value of Cohen Kappa coefficient. To determine the quality of validity and reliability of the study, the researcher also conducts validity and reliability determination techniques as suggested by Merriam (2009) through audit trail techniques, triangulation, participant review, long-term observation in the field and collaboration with participants. Overall the findings of this study have contributed to some new findings. Among the main result, researcher had found that these symptoms have started from childhood, adolescence to adulthood and among the main factors these symptoms start from self, family, environment and friends. The second finding obtained in this study is that there are two main beliefs that cause the occurrence of transgender symptoms of mak nyah, namely issues related to understanding and appreciation in concept of al-Ilahiyyah and al-Sam’iyyah. Meanwhile, in the third finding, the concept of repentance that has been introduced by al-Imam al-Ghazali in the deliberation of the science of faith can be applied to the transgender mak nyah through the practice of Mujahadah, Muhasabah, Mu’aqobah and Muroqobah. Keywords: Faith, Transgender Mak Nyah, Faith Issues, Imam al-Ghazali's Concept of Repentanc.